2018
DOI: 10.1186/s13018-017-0704-y
|View full text |Cite
|
Sign up to set email alerts
|

The titanium elastic nail serves as an alternative treatment for adult proximal radial shaft fractures: a cohort study

Abstract: BackgroundTo investigate whether closed reduction and internal fixation (CRIF) with titanium elastic nails (TENs) is a viable alternative treatment in proximal radial fractures.MethodsIn Kaohsiung Veterans General Hospital, from November 2013 to April 2015, five adult male patients with forearm injuries (average age 43 years; range 35–64 years) were treated for proximal radial shaft fractures. CRIF with TENs for radial shaft fractures was performed in these five patients. Radiographs; range of motions; visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The biomechanical principle underlying TEN involves the symmetrical bracing effect achieved by inserting these nails into the metaphysis [7] . Here, they exert pressure against the internal bone structure at 3 distinct points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomechanical principle underlying TEN involves the symmetrical bracing effect achieved by inserting these nails into the metaphysis [7] . Here, they exert pressure against the internal bone structure at 3 distinct points.…”
Section: Discussionmentioning
confidence: 99%
“…Here, they exert pressure against the internal bone structure at 3 distinct points. This technique provides immediate stability to the affected bone segment, enabling patients to mobilize early and resume their normal activities with a minimal risk of complications [7] . While TENs may not provide substantial axial and rotational stability, they offer relative stability conducive to secondary bone healing [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Lascombes and Metaizeau found 92% of their 80 patients had excellent results following intramedullary forearm nailing in both bones [14] Prakriti et al conducted a study among the adult Indian population and found 46.67% of their patients had good outcomes and 30% had excellent outcomes using the Grace and Eversman scoring system [22] . Ying-Cheng Huang et al, among the elder Taiwanese population, also concluded that TENS led to better outcomes using the Quick-Dash score, with a score of 7.92 (range 4.5-25, with lower scores indicating better outcomes) [23] .…”
Section: Discussionmentioning
confidence: 99%
“…e stability gets further augmented when one of the two bones of the forearm is xed with plate osteosynthesis. e usual period of immobilization in such xation is up to four weeks and functional outcomes do not vary much with fracture displacement [10,18]. e application of TENs for xation of proximal radial sha fractures has been shown to have favorable functional outcomes in the past few studies [5,6,7] Although the union was delayed in 5 cases in the hybrid xation group, none of the patients developed non-union.…”
Section: Discussionmentioning
confidence: 99%
“…e fracture healing occurs on the principles of relative stability and additional protection to the fracture can be provided by a long-arm cast or splint. However, there is paucity in literature regarding the use of hybrid xation in adult both bone forearm fractures [10]. We a empted to explore the outcomes of hybrid xation with titanium elastic nail system (TENs) for radial sha fractures and standard plating ( compression or bridge mode ) for ulnar fractures in adult both bone forearm fractures involving proximal half of the radial sha and compared the radiological and functional outcomes with a control group that was treated with standard plating for both the fractures.…”
Section: Introductionmentioning
confidence: 99%